Research of Automobile Flows by Imitation Simulation - Horbova, O. V; Merzlyi, O. D (Science and Transport Progress, 2021)
Purpose. Road transportation has become a very important part of the transportation process and interaction with all modes of transport, carrying out the transportation of goods and passengers. Due to the increase in traffic flows in the transport network, the problem of their rational organization is urgent. However, taking into account the influence of various factors, such as the congestion of the road section, the condition of the road, this problem cannot be solved using analytical models based on graph models. The purpose of solving the problem is to develop a safe traffic model by the method of simulation of coordinated traffic flows in the urban road network and to develop a computer simulation system necessary to achieve this purpose. Methodology. To search for effective strategies for controlled traffic flows in a megalopolis, optimal solutions for the design of the road network and traffic management, it is necessary to take into account a wide range of traffic flow characteristics, the regularities of the influence of external and internal factors on the dynamic characteristics of a mixed traffic flow. The use of modeling and the creation of an adequate model of traffic flow is an urgent task in the process of organizing and managing traffic. The research methodology will make it possible to create an integrated approach to solving problems of the given type and will contain a symbiosis of theoretical and experimental research. Findings. During the experiments, it was found that with the normal operation of the transport network, the travel speed of the entire mode of transport is satisfactory. With the appearance of factors creating a large load, the travel time of the entire mode of transport increases. We have identified the factors that can affect the optimal operation of the network, even under heavy load. Originality. For the first time the general methodology of simulation modeling was created and the formalization of the agent-based modeling method was improved. Practical value. The results of the work are used as the basis for a system of simulation modeling of traffic flows, which makes it possible to analyze the properties of existing and projected transport hubs. The system is implemented in the form of a software package that can be used in public administration institutions, design organizations and consulting companies involved in the design and reorganization of traffic patterns. The proposed agent model can be used as part of more complex simulation models of organizational and technical systems.